Under the Palm Trees : Modern Iraqi Art with Mohamed Makiya and Jewad Selim - Naji, Ahmed; Makiya, Mohamed; Selim, Jewad (NY; Rizzoli, 2018)
This richly illustrated volume explores creativity in twentieth-century Iraqi art through the art collection of a pioneer architect. Featuring works from artists such as Jewad Selim from the 1940s, the Baghdad Modern Art Group from the 1950s and 1960s and Iraqi artists in exile from 1980 onward, this volume showcases the collaboration of pioneer architect Mohamed Makiya with the Iraqi artists of his time, shedding light on the relationship between art and architecture and its role in shaping modern Iraqi society. Moreover, the Makiya collection gives a glimpse of the trajectory of Iraqi art during the first half of the twentieth century. It also introduces Mohamed Makiya, a promoter of the art of his own country, to a wider global audience.
English
Keywords: 20th century; Modern art; N5300-7418 Visual Arts- History; Iraq